In Vitro Biological Evaluation of an Alginate-Based Hydrogel Loaded with Rifampicin for Wound Care - Tudor Bibire; Radu Dănilă; Cătălina Natalia Yilmaz; Liliana Verestiuc; Isabella Nacu; Ramona Gabriela Ursu; Cristina Mihaela Ghiciuc (MDPI AG, 2024)
We report a biocompatible hydrogel dressing based on sodium alginate-grafted poly(N-vinylcaprolactam) prepared by encapsulation of Rifampicin as an antimicrobial drug and stabilizing the matrix through the repeated freeze-thawing method. The hydrogel structure and polymer-drug compatibility were confirmed by FTIR, and a series of hydrogen-bond-based interactions between alginate and Rifampicin were identified. A concentration of 0.69% Rifampicin was found in the polymeric matrix using HPLC analysis and spectrophotometric UV-Vis methods. The hydrogel's morphology was evaluated by scanning electron microscopy, and various sizes and shapes of pores, ranging from almost spherical geometries to irregular ones, with a smooth surface of the pore walls and high interconnectivity in the presence of the drug, were identified. The hydrogels are bioadhesive, and the adhesion strength increased after Rifampicin was encapsulated into the polymeric matrix, which suggests that these compositions are suitable for wound dressings. Antimicrobial activity against S. aureus and MRSA, with an increased effect in the presence of the drug, was also found in the newly prepared hydrogels. In vitro biological evaluation demonstrated the cytocompatibility of the hydrogels and their ability to stimulate cell multiplication and mutual cell communication. The in vitro scratch assay demonstrated the drug-loaded alginate-grafted poly(N-vinylcaprolactam) hydrogel's ability to stimulate cell migration and wound closure. All of these results suggest that the prepared hydrogels can be used as antimicrobial materials for wound healing and care applications.